Integrating Kahoot into Learning Management: Enhancing Student Motivation through Interactive Classroom Strategies - Faizatul Widat; Nur Aliffia Shafilla; Isyatur Rodiah (Al-Qalam Institue, 2025)
This study explores the use of Kahoot as an interactive learning tool to enhance student motivation in Social Studies. Motivated by the low enthusiasm and passive participation often observed in conventional, theory-heavy Social Studies lessons, the research adopts a descriptive qualitative case study approach. The study involved 25 students and followed a cycle of planning, action, observation, and reflection. Data were collected through observation, interviews, and documentation. Findings indicate a significant increase in student motivation and engagement. Students demonstrated greater enthusiasm, active participation, and curiosity during lessons using Kahoot. The gamified quiz environment created a fun, competitive learning atmosphere and allowed real-time assessment of student understanding. Beyond improving classroom dynamics, the study highlights critical implications for educational management. Integrating digital tools like Kahoot into classroom practice can serve as a strategic component in learning management, promoting a more student-centered, participatory, and data-informed teaching process. Educators and school leaders are encouraged to incorporate gamification strategies to support motivation and foster a culture of active learning. Kahoot proves to be not only a teaching aid but also a managerial tool for enhancing instructional planning, engagement tracking, and performance evaluation.